The photoreceptor protective cGMP‐analog Rp‐8‐Br‐PET‐cGMPS interacts with cGMP‐interactors PKGI, PDE1, PDE6, and PKAI in the degenerating mouse retina. Issue 8 (29th March 2023) - Rasmussen, Michel; Tolone, Arianna; Paquet‐Durand, Francois; Welinder, Charlotte; Schwede, Frank; Ekström, Per
Abstract: The inherited eye disease retinitis pigmentosa (RP) causes the loss of photoreceptors by a still unknown cell death mechanism. During this degeneration, cyclic guanosine‐3′, 5′‐monophosphate (cGMP) levels become elevated, leading to over‐activation of the cGMP‐binding protein cGMP‐dependent protein kinase (PKG). cGMP analogs selectively modified to have inhibitory actions on PKG have aided in impeding photoreceptor death, and one such cGMP analog is Rp‐8‐Br‐PET‐cGMPS. However, cGMP analogs have previously been shown to interact with numerous targets, so to better understand the therapeutic action of Rp‐8‐Br‐PET‐cGMPS, it is necessary to elucidate its target‐selectivity and hence what potential cellular mechanism(s) it may affect within the photoreceptors. Here, we, therefore, applied affinity chromatography together with mass spectrometry to isolate and identify Rp‐8‐Br‐PET‐cGMPS interactors from retinas derived from three different murine RP models (i.e., rd1, rd2, and rd10 mice). Our findings revealed that Rp‐8‐Br‐PET‐cGMPS bound seven known cGMP‐binding proteins, including PKG1β, PDE1β, PDE1c, PDE6α, and PKA1α. Furthermore, an additional 28 proteins were found to be associated with Rp‐8‐Br‐PET‐cGMPS. This latter group included MAPK1/3, which is known to connect with cGMP/PKG in other systems. However, in organotypic retinal cultures, Rp‐8‐Br‐PET‐cGMPS had no effect on photoreceptor MAPK1/3 expression or activity. To summarize, Rp‐8‐Br‐PET‐cGMPS is more target specific compared to regular cGMP. Abstract : cGMP can bind 13 various interactors in the retina such as PKGI/II, PKAI/II, PDE1, 2, 3, 5, and 6, as well as EPAC2. However, the promising neuroprotective Rp‐8‐Br‐PET‐cGMPS analog shows target specificity within the photoreceptors and only showed to bind seven known cGMP‐binding proteins, including PKGI, PDE1, PDE6, and PKAI.